Impact of Information Technology on the Job Satisfaction of LIS Professionals: A Case Study of Jammu & Kashmir - Pandita, Ramesh K; Dominic, J. (DESIDOC Journal of Library & Information Technology, 2018)
Based on the primary data collected from the library and information science professionals working in the higher education sector of the Jammu and Kashmir, the study aims to assess, as how far the application of information and communication technology apart from improving the library services and activities, has been instrumental in improving the job satisfaction among the library and information professionals. In all 264 responses were generated from the respondents, a whopping, 68.9 per cent respondents are of the view that library and information science professionals contribute significantly into the teaching and research activities of their institution. 61 per cent respondents have shown satisfaction with the information technology infrastructure in their respective libraries, while as, 60.2 per cent respondents are of the view that the application of information technology in libraries contribute to the job satisfaction of library professionals. Still more, 43.9 per cent respondents viewed that the library professionals working in the manual environment show lower levels of job satisfaction.